Impact Assessment of Iron and Folic Acid Supplementation with and Without Intensive Health Education in Pregnant Women of Rural Area of District Etawah: An Interventional Study - Kumar, Gaurav; Rani, Vidya; Singh, Naresh Pal; Shukla, Sushil Kumar; Kumar, Ajai; Goswami, Dolly (Indian Journal of Community Health, 2024)
Background: Low birth weight , post-partum haemorrhage still births and maternal deaths are associated with anaemia in pregnancy. If prevalence of anemia will be reduced then there will be improvement in maternal and child health and its outcome. Aim & Objectives: To evaluate the changes in the hematological profile of the study subjects and to determine the impact of intensive health education intervention on anemia status of pregnant women. Methodology: A Community based interventional study was conducted among 200 Pregnant women of selected villages in rural area of Etawah district (100 women in each interventional and non-interventional group) using a self-developed, pre designed, pretested, structured and validated questionnaire. statistical package for social sciences (SPSS) software was used to analyse the data. Result: After health education intervention there is significant increase in the haematological profile of study participants of interventional group (p<0.05) as before intervention values of mean Hb was 10.58±1.79 gm/dl which became 11.72±1.48 gm/dl There were 34 (73.9%) participants in the interventional group that were originally anaemic before the study, but after the intervention, they became non-anaemic. Conclusion: Health education sessions helped the pregnant women to improve their knowledge regarding anemia in pregnancy, as well as improve their ability to select iron rich foods, increase compliance with iron supplementation, and raise their haemoglobin levels.